Modeling and switching simulation tool of SiC-GTO / Mohd Shawal Jadin, Muhamad Zahim Sujod and Raja Mohd Taufika Raja Ismail - Jadin, Mohd Shawal; Sujod, Muhamad Zahim; Raja Ismail, Raja Mohd Taufika (UiTM Press, 2008)
Power semiconductor devices such as Thyristor, GTO, IGBT and Power MOSFET become important devices in high voltage and high frequency power electronics applications. Recent development in power electronics has made power semiconductor devices larger and more complicated, and therefore, device simulation is necessary to predict their characteristics. From the fundamental equations of semiconductor devices, potential distribution and carrier concentrations can be solved using the Finite Element Method (FEM) [1]. Silicon Carbide (SiC) material has been utilized for power devices, in order to achieve fast switching time and low switching loss. In this study, we analyzed the physical constants and device characteristics of Silicon Gate Turn-off (Si-GTO) thyristor and SiC-GTO. We build a GTO model by set up the boundary conditions, dimensions and adapt a suitable doping profile into the device model. We also compare the switching waveforms of Si-GTO and SiC-GTO. Results show that turn-off time of SiC-GTO is decreased extremely. We use our simulation tools in running all the modeling and switching simulation process.